Pertumbuhan dan tipologi pertumbuhan sektor pertanian Kabupaten Tanjung Jabung Barat - Mahdi Mahdi; Amril Amril; Syaifuddin Syaifuddin (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2017)
This study aims to analyze the growth rate of GRDP in the agricultural sector and the typology of its growth in Tanjung Jabung Barat District. The data used are secondary data of Tanjung Jabung Barat Regency for the period 2000 - 2013. Data is sourced from the Central Bureau of Statistics of Tanjung Jabung Barat Regency and Jambi Province. Data were analyzed descriptively using the Klassen growth typology model. The results of the study found: 1) the average growth rate of the agricultural sector GRDP of Tanjung Jabung Barat District during the period 2000 - 2013 was 8.25 percent per year. In the same period, almost all sub-sectors of agriculture experienced an increase except for the forestry sub-sector which experienced a decline; 2) based on Klassen's growth typology analysis, the agricultural sector of Tanjung Jabung Barat Regency is classified as a criterion of advanced and fast-growing sectors